2018
DOI: 10.1016/j.cell.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry-First Approach for Nomination of Personalized Treatment in Lung Cancer

Abstract: Diversity in the genetic lesions that cause cancer is extreme. In consequence, a pressing challenge is the development of drugs that target patient-specific disease mechanisms. To address this challenge, we employed a chemistry-first discovery paradigm for de novo identification of druggable targets linked to robust patient selection hypotheses. In particular, a 200,000 compound diversity-oriented chemical library was profiled across a heavily annotated test-bed of >100 cellular models representative of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 35 publications
2
90
0
Order By: Relevance
“…GDRC also correlated positively with EGFR phosphorylation at Y1173 (pY1173), a marker for EGFR signaling and Gefitinib sensitivity ( Figure 5C ). Finally, comparing metabolic features with high-throughput drug sensitivity data (McMillan et al, 2018) revealed that GDRC cell lines tend to be sensitive to the EGFR inhibitor Erlotinib; these cell lines have low areas under the Erlotinib dose-response curve (AUC) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…GDRC also correlated positively with EGFR phosphorylation at Y1173 (pY1173), a marker for EGFR signaling and Gefitinib sensitivity ( Figure 5C ). Finally, comparing metabolic features with high-throughput drug sensitivity data (McMillan et al, 2018) revealed that GDRC cell lines tend to be sensitive to the EGFR inhibitor Erlotinib; these cell lines have low areas under the Erlotinib dose-response curve (AUC) ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…As our 2D co-culture system enables easy tracking of the growth dynamics of chemosensitive and chemoresistant cells under simple epifluorescence microscopy, we can further optimize them for high throughput screening purposes to identify optimal combinatorial therapies and discovery of new treatment strategies via screening of experimental small molecule libraries (34). Our 2D co-culture system also provides us the control to build various types of spatial architecture by simply changing the location of initial inoculation (Fig 6).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on lung cancer patient selection demonstrates that the traditional "chemistry-first" approach can be sustained as long as biomarkers, genomewide targets and genetic landscapes are included in the models. 165 Biological embeddings may help to generalize this approach, smoothing the transition from the blockbuster system of drugs to a personalized medicine one. 166…”
Section: Discussionmentioning
confidence: 99%
“…All in all, as pharmaceutical research is moving towards precision medicine, there is a need to enrich computational methods with generic knowledge of biology as well as patient‐ and cohort‐specific samples. Recent work on lung cancer patient selection demonstrates that the traditional “chemistry‐first” approach can be sustained as long as biomarkers, genome‐wide targets and genetic landscapes are included in the models . Biological embeddings may help to generalize this approach, smoothing the transition from the blockbuster system of drugs to a personalized medicine one …”
mentioning
confidence: 99%